Pengaruh Viral Marketing, Social Media Influencer dan Online Customer Review Terhadap Purchase Intention Maybelline Superstay Vinyl Ink pada Mahasiswa UPN Veteran Jatim - Lidia Angelina; Ugy Soebiantoro; Nurkholish Majid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of viral marketing, social media influencers, and online customer reviews on purchase intention for Maybelline Superstay Vinyl Ink products among UPN "Veteran" East Java students. The research method used is quantitative with data collection techniques through distributing questionnaires to the student population of UPN "Veteran" East Java with a sample of 140 respondents. using purposive sampling technique. Data were analyzed using PLS-SEM with the help of SmartPLS software. The research results show that viral marketing does not contribute to purchase intention, while social media influencers and online customer reviews contribute to purchase intention. These findings indicate that influencer recommendations and customer reviews have an important role in shaping purchase intention towards cosmetic products among students compared to the success of viral marketing.